2023
DOI: 10.1111/1365-2656.13891
|View full text |Cite
|
Sign up to set email alerts
|

Predation cues amplify the effects of parasites on the personality of a keystone grazer

Abstract: 1. Parasites can alter species interactions either by modifying infected host behaviour or by influencing behavioural responses in uninfected individuals. Salt marsh ecosystems are characterized by a predator-prey interaction between the keystone grazer, Littoraria irrorata, and its main predator, Callinectes sapidus, both integral players in mediating the productivity of these habitats. 2. Littoraria also acts as the first intermediate host for at least four species of digenetic trematode. Parasite infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
(170 reference statements)
0
4
0
Order By: Relevance
“…This is in line with previous investigations in this system on the trait‐mediated reductions in the top–down impacts of snails on cordgrass biomass by P. acanthus (Morton 2018, Morton and Silliman 2020). However, recent laboratory behavioral assays investigating the influence of trematode parasitism on Littoraria boldness found that infected snails influenced predator avoidance behaviors in healthy conspecifics in high risk environments (Salerno et al 2023). It is possible that infected snails may yield outsized effects by influencing the behavior of conspecifics under certain circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous investigations in this system on the trait‐mediated reductions in the top–down impacts of snails on cordgrass biomass by P. acanthus (Morton 2018, Morton and Silliman 2020). However, recent laboratory behavioral assays investigating the influence of trematode parasitism on Littoraria boldness found that infected snails influenced predator avoidance behaviors in healthy conspecifics in high risk environments (Salerno et al 2023). It is possible that infected snails may yield outsized effects by influencing the behavior of conspecifics under certain circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Population‐level effects likely reverberate through communities and ecosystems when such changes impact hosts' heterospecific interactions, such as predator–prey encounters and heterospecific communication. Salerno et al (2023) found that the presence of predator cues and infected conspecifics together drive phenotypic outcomes, such as personality, in snails. An understanding of the complex spatial interactions between predators and parasites in a given habitat (the overlaid ‘landscape of fear’ and ‘landscape of disgust’; Buck et al, 2018) will be critical for predicting variation within and among hosts, especially in variable environments.…”
Section: Biological Levels Of Variationmentioning
confidence: 99%
“…Recognition of the pivotal role that parasites play in the variability of animal phenotypes in nature is surprisingly low (Chretien et al, 2023). Several contributions to this special feature present practical guidance for researchers working in a range of disciplines to assess the role of infection in their study system, including behaviour (Salerno et al, 2023; Stockmaier et al, 2023; Tillman & Adelman, 2023; Vindas et al, 2023), performance (Chretien et al, 2023), physiology (Alves & Aubin‐Horth, 2023; Lopes, 2023; Seguel et al, 2023; Wu, 2023) and epigenetics (Ngo et al, 2023). Yet, there are still many unanswered questions.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation